The gut microbiota and healthy aging: insights from bacterial evolution - Miranda, Rita de Melo (2025)
The gut microbiota is a complex ecosystem influenced by both external factors, such as dietary intake, and internal physiological changes, particularly aging. While the impact of these factors on the gut microbiota is often studied at the community level, there is comparatively less focus on understanding how they serve as selective pressures driving the evolution of individual microbial species. This thesis explored the evolutionary dynamics of the gut microbiota, focusing on Escherichia coli under selective pressures such as diet, aging, and exercise during aging. Using mouse models, the research aims to understand how these factors shape microbial evolution and potentially influence healthy aging. Chapter 2 examined the role of the lac operon in E. coli, which allows for lactose metabolism, in the young adult mammalian gut. Our results showed that the lac operon provides a competitive advantage in the presence of lactose but becomes neutral once lactose is no longer available. Additionally, this study highlighted how microbial interactions within the gut ecosystem, particularly the presence of other bacteria, can modulate this advantage, indicating that both diet and the microbial environment play fundamental roles in shaping microbial evolution. In Chapter 3, the focus shifted to aging and its impact on microbial evolution. Besides several other aging hallmarks, aging is associated with the onset of chronic low-grade inflammation (inflammaging), increased gut permeability, and changes in microbiota composition. By tracking the evolution of E. coli in the guts of young, old, and very old mice, this study revealed that aging, even in healthy conditions, selects for increased motility and biofilm formation—traits that are typically associated with pathogenicity. These findings suggest that the aging gut creates an environment that favors the emergence of pathoadaptive traits, with yet unknown consequences for the host. Curiously, however, this study also found that young and very old mice shared common adaptive mutations in E. coli that were absent in the old, suggesting more shared similarity between these two gut environments, which was corroborated by their gut metabolic environment. Chapter 4 built on findings from Chapter 3 and explored the role of long-term voluntary exercise in modulating microbial evolution in aging hosts. Among several other beneficial effects, exercise has been shown to reduce inflammation, improve muscle function, influence gut health and the gut microbiota. This study corroborated these findings, while also revealing that exercise impacts the microbiota at the strain level, as shown by the evolutionary pattern of E. coli. Specifically, exercised mice exhibited delayed or attenuated sarcopenia and reduced systemic inflammation, as well as enhanced gut microbiota resilience. The evolutionary trajectories of E. coli in exercised mice pointed to adaptive pathways which included a shift toward anaerobic metabolism, and a decrease in the selection of some, but not all, of the pathoadaptive traits commonly seen in sedentary aging hosts. Collectively, the findings from this thesis highlight the dynamic relationship between host physiology and microbial evolution, revealing how diet, aging, and exercise can shape microbial communities in the gut. These results may have broader implications for developing strategies to maintain gut health and promote healthy aging, with potential applications of interventions like physical activity to modulate the gut microbiota and delay the onset of age-related diseases.